Cellular - Schwartz, Ellen, 1949- (Orca soundings, 2010)
Brendan, the popular captain of the basketball team, rejects all offers of help after being diagnosed with leukemia and decides to face chemotherapy alone, but his attitude changes when he meets Lark, a girl who remains positive and hopeful even though her condition is much worse than his.